No Detection of Crimean-Congo Hemorrhagic Fever Virus in Hard Ticks (Ixodidae) from a Highly Endemic Area in Southeast Iran - Sahar Asadolahizoj1; Dariush Saadati2; Mehdi Rasekh3; Faezeh Faghihi4; Mehdi Fazlalipour5; Amirsajad Jafari6 (Journal of Medical Microbiology and Infectious Diseases)
Introduction: Crimean-Congo Hemorrhagic Fever (CCHF) is a zoonotic viral infection transmitted mainly via CCHF virus-infected ticks between vertebrate hosts. The disease occurs in almost all provinces of Iran. This study investigated the CCHFV infection in hard ticks collected from livestock in the Sistan region of Sistan and Baluchestan Province, southeast of Iran. Methods: In this study, ticks were collected from 220 livestock, including 150 sheep, 50 goats, 20 cows in five counties of Sistan Province (Zabol, Zehak, Hirmand, Nimruz, and Hamun). The ticks were identified under a stereomicroscope according to valid morphological keys. A reverse transcription-polymerase chain reaction (RTPCR) method was used to detect the CCHFV genome via amplifying the S segment. Results: Among 100 selected ticks, RT-PCR revealed no CCHFV infection. Conclusion: Although no ticks were positive for CCHFV, it should be recalled that Sistan and Baluchestan province is among the highly endemic CCHF foci. As a result, further investigation and larger sample sizes are required to confirm our outcome. According to the hypothesis that direct contact with viremic livestock is more significant than tick bites in the viral transmission, more serological and molecular screening should be performed on high-risk individuals, e.g., slaughterhouse staff, ranchers, farmers, and veterinarians in the Sistan region.